2006
DOI: 10.1111/j.1540-8167.2006.00464.x
|View full text |Cite
|
Sign up to set email alerts
|

Temporary Esophageal Stenting Allows Healing of Esophageal Perforations Following Atrial Fibrillation Ablation Procedures

Abstract: Early diagnosis of esophageal perforations following LACA may allow temporary esophageal stenting with successful esophageal healing. Prompt chest CT scans with oral and i.v. contrast should be considered in any patient with sub-sternal chest pain or dysphagia following LACA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
92
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(95 citation statements)
references
References 34 publications
2
92
1
Order By: Relevance
“…If the atrio-esophageal perforation can be detected before it begins forming a fistula, treatment with temporary esophageal stenting may be useful. 45 To avoid an atrio-esophageal fistula, understanding the relationship between the esophagus and LA is paramount. Lenola et al 46 reported the topographic anatomy of the esophagus and posterior LA by using a 16-row multidetector CT scanner in patients with AF undergoing a percutaneous catheter ablation procedure.…”
Section: Atrio-esophageal Fistulamentioning
confidence: 99%
“…If the atrio-esophageal perforation can be detected before it begins forming a fistula, treatment with temporary esophageal stenting may be useful. 45 To avoid an atrio-esophageal fistula, understanding the relationship between the esophagus and LA is paramount. Lenola et al 46 reported the topographic anatomy of the esophagus and posterior LA by using a 16-row multidetector CT scanner in patients with AF undergoing a percutaneous catheter ablation procedure.…”
Section: Atrio-esophageal Fistulamentioning
confidence: 99%
“…[6][7][8][9][10] Alternatively, successful stenting of an esophageal perforation without communication with the atrium or the pericardium has been described. 11 Advantages from stenting arise from quick establishment of a barrier that minimizes air and solid material embolism without the risks of esophageal surgery. However, other reports describe fatal complications caused by air insufflation during upper gastrointestinal endoscopy or stent dislocation leading to insecurities of adapting this approach in patients with esophageal perforations.…”
Section: Clinical Perspective On P 681mentioning
confidence: 99%
“…However, only patients with isolated perforation without pericardial or atrial communication have been successfully treated with this approach. 11,25,26 In patients with esophagopericardial and esophagoatrial fistulas, fatal courses or the necessity of combining stenting with surgery have been described. 6,12,24,27 Besides this, there is growing experience with esophageal stenting in the context of iatrogenic perforations because of endoscopic procedures.…”
Section: Treatment Of Esophagopericardial Fistulasmentioning
confidence: 99%
“…If I-MRI is clinically used, its use may reduce the AF recurrence rate (currently 10% to 30%) after ablation procedures. [11][12][13][14] I-MRI may also reduce complications, such as unwanted heating of adjacent organs, perforation of the esophagus, 15 PV stenosis, or clot formation. 16 -18 In an earlier study, 19 an EAM mapping system for use inside an MR scanner was presented.…”
Section: Clinical Perspective On P 704mentioning
confidence: 99%